Faktor-Faktor Yang Berhubungan Dengan Terjadinya Stroke Berulang Pada Penderita Pasca Stroke - SARI, Indah Permata; , Umi Budi Rahayu SST FT, M.Kes; , Isnaini Herawati, S.Fis., M.Sc (2015)
Background: Stroke is a condition that occurs when blood flow to a part of the brain which is suddenly disrupted. While recurrent stroke is a stroke that occurred after the first stroke occurs as a result of lack of self control from the patients and the low level of awareness of stroke risk factors. Stroke risk factors that cannot be modified: age, gender, family history of stroke, and the tribe. Stroke risk factors that can be modified: hypertension, heart disease, diabetes mellitus, hyper cholesterol, obesity, smoking, alcohol consumption, unhealthy lifestyle, and stress. The risk factors of stroke that occurs in general: drugs, head and neck injury, and infection. Stroke risk factor for women: the use of oral contraceptives, pregnancy and childbirth, menopause. Objective: This study was aimed to determine the factors associated with the occurrence of recurrent stroke and determine the order of the factors that cause the occurrence of recurrent stroke. Methods: This study was done by a cross sectional observation by using quantitative method, and data analysis done by using Chi Square test. The number of samples in this study is 50 people. Results: Statistical test done by using Chi Square obtained p value: 0.021 or p <0.05 Ha accepted means there is a family history of stroke with recurrent strokes. The p-value: 0.022 or p <0.05 Ha accepted which means that there is a relationship between hypertension and recurrent stroke. The p-value: 0.048 or p <0.05 Ha accepted which means that there is a relationship of smoking with recurrent strokes. The p-value: 0.039 or p <0.05 Ha accepted which means that there is a relationship between stress and recurrent strokes. Based on the analysis of the data showed that factors associated with the occurrence of recurrent stroke toward patients with post-stroke is a family history of stroke, hypertension, smoking, and stress. Conclusions: Factors associated with the occurrence of recurrent stroke toward patients with post-stroke which is significance after tested by using Chi Square test are family history of stroke, hypertension, smoking, and stress